2020
DOI: 10.3389/fevo.2020.580701
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Adaptation to Temperature via a Potential Genomic Island of Divergence in the Invasive Green Crab, Carcinus maenas

Abstract: Widespread species often adapt easily to novel conditions – both those found in new habitats and those generated by climate change. However, rapid adaptation may be hindered in the marine realm, where long-distance dispersal and consequently high gene flow are predicted to limit potential for local adaptation. Here, we use a highly dispersive invasive marine crab to test the nature and speed of adaptation to temperature in the sea. Using single nucleotide polymorphisms (SNPs) generated from cardiac transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 69 publications
(99 reference statements)
1
15
0
Order By: Relevance
“…Assuming similar behavior in an ancestor of S. cerevisiae before the rise of its modern thermotolerance profile, we infer that the latter event was unlikely to be precipitated by a single jump to a hot growth environment, long ago in history. Rather, we favor the hypothesis that thermotolerance evolution through the S. cerevisiae lineage proceeded along a temperature cline, as has been documented in elegant local-adaptation case studies (Mimura et al 2013; Robin et al 2017; Dudaniec et al 2018; Key et al 2018; Tepolt and Palumbi 2020). In this scenario, a well-adapted ancestral S. cerevisiae population in a given temperature niche would have acquired variants that resolved defects manifesting in slightly warmer conditions, and expanded its range.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Assuming similar behavior in an ancestor of S. cerevisiae before the rise of its modern thermotolerance profile, we infer that the latter event was unlikely to be precipitated by a single jump to a hot growth environment, long ago in history. Rather, we favor the hypothesis that thermotolerance evolution through the S. cerevisiae lineage proceeded along a temperature cline, as has been documented in elegant local-adaptation case studies (Mimura et al 2013; Robin et al 2017; Dudaniec et al 2018; Key et al 2018; Tepolt and Palumbi 2020). In this scenario, a well-adapted ancestral S. cerevisiae population in a given temperature niche would have acquired variants that resolved defects manifesting in slightly warmer conditions, and expanded its range.…”
Section: Discussionmentioning
confidence: 58%
“…However, we have as yet little insight into the ecological dynamics by which this model trait evolved along the S. cerevisiae lineage. Cases of adaptation across temperature clines are a mainstay of the evolutionary genetics literature (Turner et al 2008;Prasad et al 2011;Mimura et al 2013;Savolainen et al 2013;Robin et al 2017;Dudaniec et al 2018;Key et al 2018;Endler 2020;Tepolt and Palumbi 2020;Calfee et al 2021;Machado et al 2021). Here we sought to explore the relevance of such a mechanism to the events by which S. cerevisiae gained its maximal thermotolerance phenotype.…”
mentioning
confidence: 99%
“…Finally, many of the same SNPs found in the inferred inversion driving latitudinal divergence were previously identified as belonging to a putative supergene strongly associated with thermal physiology in a data set spanning six native‐ and invasive‐range C . maenas populations (Tepolt & Palumbi, 2020). While winter SST and latitude cannot be disentangled in our current data set, this previous study provided stronger evidence for temperature in driving selection.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously proposed that a chromosomal inversion or another genomic region of reduced recombination is probably under selection to temperature in C . maenas (Tepolt & Palumbi, 2020). Many of the same SNPs identified in the inferred inversion in this study were independently found to be part of the putative inversion in that prior global study, indicating that the same probable inversion is associated with cold tolerance globally and with latitudinal divergence along the northeast Pacific.…”
Section: Discussionmentioning
confidence: 99%
“…Hodgins et al (2015) compared transcriptomes across 35 species of plants in the Asteraceae, including six major invasive species. They found no support for the idea that there was consistent selection on genes that contributed to invasiveness [but see opposite results with a similar approach in the invasive green crab, Carcinus maenas (Tepolt and Palumbi, 2020)]. In a rare comparison of sequence variation and expression variation, a study of two independent invasions of the Pacific Oyster (Crassostrea gigas) into the North Sea found little overlap between differentially expressed genes and outlier loci.…”
Section: Discoveries and Limitations Of Genomic Studies Of Diverse Invasive Speciesmentioning
confidence: 98%